Give and take : a revolutionary approach to success - Grant, Adam. 1981- (Viking, 2013)
Using his own cutting-edge research as a professor at Wharton Business School, Adam Grant shows how helping others can lead to greater personal success. He demonstrates how smart givers avoid becoming doormats, and why this kind of success has the power to transform not just individuals and groups, but entire organisations and communities.